KONTRIBUSI 'URF DALAM PENGEMBANGAN FIIQH ISLAM - Ayoeb Amin (Jurnal Hukum, 2005)
Allah  sent  dawn  the  revelation,  that  is  Qur'an and  Sunnah  as  law resources  in Islam.   Fiqh  is the results of the  interpretation for texts  of the Qur'an  and  Sunnah.  Man  who  interpreted  such  texts  of the  Qur'an  and Sunnah  was  under  the  influence  of the several  factors,  among  others  'urf. The  'urf  is the   basis  of  law enforcement, which  is not mentioned  in the Qur'an  and  Sunnah.     The   'urf   plays  agreat   role  in  law  enforcement, especially   in   the   muamalah   duniawiyah.   Therefore,   the   'urf  makes   a significant contribution to the Islamic fiqh development.